2018
DOI: 10.1590/1806-9061-2018-0730
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnostic of Chicken Parvovirus (ChPV) Affecting Broiler Flocks in Ecuador

Abstract: Enteric diseases affect poultry and cause important economic losses in many countries worldwide. Avian parvovirus has been linked to enteric conditions, such as malabsorption and runting-stunting syndrome (RSS), characterized by diarrhoea, and reduced weight gain and growth retardation. In 2013 and 2016, 79 samples were collected from different organs of chickens in Ecuador that exhibited signs of diarrhea and stunting syndrome, and analysed for the presence of chicken parvovirus (ChPV). The detection method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Similar results were found in the present study in which apparently healthy chickens also showed high viral concentrations [ 22 ]. ChPV has been detected in chickens independently of zootechnical interest and in many regions around the world with high chicken production, such as Europe [ 10 , 17 , 18 ], China [ 35 ], South Korea [ 36 ], North America [ 8 , 37 , 38 ], Brazil [ 9 , 16 , 24 , 25 ], and Ecuador [ 26 , 38 ]; however, its presence remains unknown in the rest of South America. The present study also showed that the virus was detected at earlier and later ages in chickens, demonstrating that virus dissemination can occur at any time [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were found in the present study in which apparently healthy chickens also showed high viral concentrations [ 22 ]. ChPV has been detected in chickens independently of zootechnical interest and in many regions around the world with high chicken production, such as Europe [ 10 , 17 , 18 ], China [ 35 ], South Korea [ 36 ], North America [ 8 , 37 , 38 ], Brazil [ 9 , 16 , 24 , 25 ], and Ecuador [ 26 , 38 ]; however, its presence remains unknown in the rest of South America. The present study also showed that the virus was detected at earlier and later ages in chickens, demonstrating that virus dissemination can occur at any time [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of these assays showed a high sensitivity for ChPV detection and quantification. In the Brazilian chicken flocks in the recent years, many outbreaks of RSS have been reported where ChPV has been detected, and the NS gene was sequenced, confirming that the sequences belonged to ChPV, identifying the virus in young and old chickens as early as the first day of infection [ 9 , 16 , 24 , 25 , 26 ]. Enteric diseases cause economic losses in poultry, the depreciation of poultry flocks, and increased susceptibility to other diseases, so a rapid, efficacious, affordable, reliable assay should be standardized for the diagnosis of the etiological agent [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 97%
“…These two viruses are widespread amongst commercial poultry, including the US, Hungary, Poland, and Croatia [ 101 105 ], and ChPV has also been reported in South Korea, China, India, Brazil, Ecuador, Canada, and the UK [ 106 112 ]. While ChPV and TuPV have been associated with malabsorption syndrome in chickens and the occurrence of enteritis in turkeys, respectively, the contribution of these viruses to disease remains unclear as they are also detected in healthy birds [ 103 , 105 , 113 – 119 ].…”
Section: Genus Aveparvovirusmentioning
confidence: 99%
“…that infect vertebrate hosts make up the subfamily Parvovirinae , while those that infect arthropods make up the subfamily Densovirinae (14). According to the latest classification by the International Committee on Taxonomy of Viruses (https://talk.ictvonline.org/taxonomy/), the Parvovirinae subfamily is divided into eight genera (58) (Amdoparvovirus, Aveparvovirus, Bocaparvovirus, Copiparvovirus, Dependoparvovirus, Erythroparvovirus, Protoparvovirus, and Tetraparvovirus). Chicken parvovirus (ChPV) and turkey parvovirus (TuPV) are classified as members of the new genus Aveparvovirus (Galliform aveparvovirus 1).…”
Section: Announcementmentioning
confidence: 99%